Measurement invariance of the teachers’ awareness scale in content-integrated education for multilingual learners - Park, Jung Yeon; Kim, Sujin; Chen, Xiaowen (Frontiers in Education, 2024)
This study validates the scale, Critical Awareness toward Content-Language Integrated Education, recently designed to assess teachers' awareness and beliefs towards Multilingual Learners (MLs) in content classrooms. By analyzing survey responses from a total of 458 teacher participants in the U.S., we examined evidence of validity, reliability, and measurement invariance. Confirmatory Factor Analysis (CFA) confirmed the three-factor structure, consisting of 34 items, with the suggestion to exclude one item out of 35 items. Multiple-group CFA (MG-CFA), considering teachers' roles and for grade-levels of teaching, confirmed partial metric invariance and scalar invariance, with the constraints on three non-invariant items being released.Following the exclusion of the three items, subsequent data analyses were performed to compare teacher subgroups based on the finalized 31-item scale. The overall findings endorse the scale's reliability and validity, supporting its applicability for researchers and practitioners in related fields.